2021
DOI: 10.3390/microorganisms9040771
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines to Prevent Meningitis: Historical Perspectives and Future Directions

Abstract: Despite advances in the development and introduction of vaccines against the major bacterial causes of meningitis, the disease and its long-term after-effects remain a problem globally. The Global Roadmap to Defeat Meningitis by 2030 aims to accelerate progress through visionary and strategic goals that place a major emphasis on preventing meningitis via vaccination. Global vaccination against Haemophilus influenzae type B (Hib) is the most advanced, such that successful and low-cost combination vaccines incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
0
9
0
2
Order By: Relevance
“…89 Development of Hia vaccines should be technically feasible, but a limited market would likely require donor support to incentivize a manufacturer. 90 An approach similar to the Hib oligomers can be envisaged. Considering the structural and infectious similarities between Hia and Hib serotypes, the success of Hib vaccination could suggest a rational background for the development of a Hia glycoconjugate vaccine protective both in adults and infants.…”
Section: Haemophilus Influenzaementioning
confidence: 99%
“…89 Development of Hia vaccines should be technically feasible, but a limited market would likely require donor support to incentivize a manufacturer. 90 An approach similar to the Hib oligomers can be envisaged. Considering the structural and infectious similarities between Hia and Hib serotypes, the success of Hib vaccination could suggest a rational background for the development of a Hia glycoconjugate vaccine protective both in adults and infants.…”
Section: Haemophilus Influenzaementioning
confidence: 99%
“…For the past two decades, high quality meningococcal glycoconjugate vaccines have been responsible for protection against significant mortality and morbidity from meningitis and septicemia [ 5 ]. Immunity generated through the development of T-cell dependent bactericidal antibody in those most at risk has resulted in reducing nasopharyngeal carriage and inducing herd immunity in highly vaccinated populations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The principal means of achieving targets to reduce cases and deaths from meningitis will inevitably be through vaccination. Alderson et al [ 6 ] gave a comprehensive overview of past and present developments in meningitis vaccines. They drew attention to the importance of low-cost vaccines for global introduction, the expanding range of conjugate vaccines and the more recently developed meningococcal protein vaccines, and the challenges in reaching prevention goals.…”
mentioning
confidence: 99%
“…Karachaliou Prasinou et al [ 8 ] showed how mathematical models can be used to optimise the effectiveness of vaccination programmes, with two key parameters being the duration of protection and age at vaccination. Such models are relevant both for the serogroup A vaccine currently being deployed in the meningitis belt and for the anticipated roll out of pentavalent (ACWXY) conjugate vaccines [ 6 ]. The need for broader-valency vaccines in the global control of invasive meningococcal disease was well demonstrated in the paper by Tzeng and Stephens [ 9 ], describing the changing epidemiology and emerging disease due to serogroups other than A, B, and C.…”
mentioning
confidence: 99%
See 1 more Smart Citation